2006
DOI: 10.1242/jcs.02707
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin stimulates internalization of ErbB2 in a proteasome-dependent way

Abstract: The potent oncoprotein and receptor tyrosine kinase ErbB2 is remarkable because it resists efficient downregulation. However, ErbB2 can be downregulated by the HSP-90 inhibitor geldanamycin, but the underlying cellular mechanisms are uncertain. Apparently, delivery of ErbB2 to lysosomes, cleavage of the ErbB2 kinase domain and proteasomal activity are all processes that are involved. Using a non-invasive confocal microscopical assay allowing quantitative analysis of ErbB2 internalization in cell populations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
95
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 36 publications
12
95
0
1
Order By: Relevance
“…We found HER2 and HSP-90 colocalized in membrane protrusions in SKBR3 cells (Fig. 5C) (12,26), but their colocalization was abolished in PMCA2KD cells (Fig. 5C).…”
Section: Pmca2 Regulates Breast Cancer Cell Growth and Tumor Formationmentioning
confidence: 85%
See 2 more Smart Citations
“…We found HER2 and HSP-90 colocalized in membrane protrusions in SKBR3 cells (Fig. 5C) (12,26), but their colocalization was abolished in PMCA2KD cells (Fig. 5C).…”
Section: Pmca2 Regulates Breast Cancer Cell Growth and Tumor Formationmentioning
confidence: 85%
“…Several groups have reported that HER2 resides within microvillus-like membrane protrusions, and Hommelgaard and colleagues hypothesized that these structures support the retention of HER2 on the cell surface (33)(34)(35)(36). Previous experiments also showed that interactions with HSP-90 are important for HER2 stabilization within membrane protrusions and its resistance to internalization (12,26). Thus, it is noteworthy that PMCA2 levels correlate with HSP-90 levels in human tumors and that knockdown of PMCA2 is associated with decreased interactions between HSP-90 and HER2, the internalization of HER2, and the disruption of the membrane protrusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that ErbB2/HER2 is a plasma protein that resists internalization and exhibits a long half-life on the surface of the cells. Because it relies on Hsp90 for stable expression, exposure of ErbB2/HER2-expressing cells to an Hsp90 inhibitor such as geldanamycin leads to rapid internalization, ubiquitination, and degradation of the protein (Mimnaugh et al 1996;Lerdrup et al 2006). Pedersen et al (2008) have argued that ubiquitination of ErbB2/HER2 following inhibition of Hsp90 is essential for presentation of the internalized protein to the lysosomes for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Pedersen et al (2008) have argued that ubiquitination of ErbB2/HER2 following inhibition of Hsp90 is essential for presentation of the internalized protein to the lysosomes for degradation. Concurrent treatment of ErbB2/HER2-expressing cells with geldanamycin and lactacystin, a well known proteasomal inhibitor, rescues ErbB2/HER2 from degradation and results in the accumulation of internalized, ubiquitinated protein (Lerdrup et al 2006). We hypothesize that accumulation of internalized and thus inactive, ubiquitinated ErbB2/HER2 protein in MCF-7 cells transfected to express ErbB2/HER2 and treated with EF leads to such an increase in the cellular stress that cells prefer to die than enter a cytostatic phase following treatment with EF.…”
Section: Discussionmentioning
confidence: 99%